Higher Cortical Dysfunction Presenting as Visual Symptoms in Neurodegenerative Diseases - Liu, Yin; Pelak, Victoria S.; van Stavern, Gregory; Moss, Heather E. (Frontiers in Neurology, 2020)
Introduction: As the population ages, increasing prevalence of neurodegenerative diseases will have profound implications for the health care system. Recognizing visual symptoms from neurodegenerative diseases can be challenging, especially in the presence of co-existing eye diseases. Methods: A seven-question survey was completed by attendees at the “neurodegenerative diseases in neuro-ophthalmology” symposium during the 2017 North American Neuro-ophthalmology Society annual meeting using a web-based audience response system. Content included demographics, patient prevalence, and perceived barriers. Results: Fifty-five practicing neuro-ophthalmologists (thirty-three ophthalmology-trained, twenty-two neurology-trained) participated in the survey. Twenty (36%) had <5 years of experience, and 19 (32%) had >15 years of experience. Forty-one (75%) reported seeing patients more than five half-day/week. Thirty (55%) reported that at least 1 of 10 or 1 of 20 new patients referred have a prior diagnosis of a neurodegenerative disease. Twenty-one (40%) of the respondents reported attributing visual complaints to higher order effects in at least 25% of patients with a prior diagnosis of neurodegenerative disease vs. five (9%) without a prior diagnosis. For those diagnosed with neurodegenerative disease by the neuro-ophthalmologist, reasons for referral were unknown cause of visual symptom (56%), to confirm diagnosis and/or treat visual complaint due to neurodegeneration (29%), and functional disorder (5%). Perceived barriers to diagnosing visual dysfunction due to neurodegenerative disease included difficulty making a referral to neuropsychologists or behavioral neurologists (73%), lack of time for in-depth assessment (62%), lack of tools to assess visual dysfunction due to neurodegenerative disease (40%), and lack of knowledge about presenting signs and symptoms (31%). Conclusion: Visual symptoms from neurodegenerative disease in patients with and without prior diagnoses of neurodegenerative disease are evaluated by neuro-ophthalmologists. Lack of time, resources, and knowledge are barriers to diagnosis. A larger study is warranted to guide programs to improve diagnosis of visual consequences of neurodegenerative disease.